A new H-section buckling-restrained brace improved by movable steel blocks and stiffening ribs. (January 2022) - Yuan, Yue; Gao, Jingwei; Qing, Yuan; Wang, Chun-Lin
Abstract: A new buckling-restrained brace with the H-section steel core (HBRB) was proposed with the outer tube as a restraining member. The inside of the upper and lower flanges of the steel core is filled with steel blocks and stiffened by closer transverse ribs to limit the local buckling of the flange. The test and the finite element analysis were implemented to evaluate the seismic performance and failure mode of the new HBRB. The results reveal that the new HBRB specimens present stable energy dissipation capacities. There is no apparent degradation of bearing capacity and stiffness until the failure of the new HBRB specimens, and the performance of the new HBRB is better than that of previous HBRB. The main reason for the failure of previous HBRB specimens is the evident inward deformation of the flange. The movable steel blocks are filled between the upper and lower flanges of new HBRBs, which can effectively restrict the inward deformation of the flanges. The multi-wave buckling deformation of the flanges and the web were observed after the test. The calculation formula of the buckling half-wavelength of the flange restrained by steel blocks is established. The flanges within the zones with closer ribs only bulged outward due to the Poisson effect of the compressed web in the test. The numerical study shows that the flange buckled inward at a larger transverse rib spacing. The calculation equation of the maximum rib spacing with the specific width-to-thickness ratio of the flange extension was given based on the numerical simulation results. Graphical abstract: Image 1 Highlights: The proposed HBRB with excellent seismic performances verified by tests. The flanges restrained by the steel blocks exhibited multiple-wave buckling. The flanges stiffened by closer ribs exhibited only outward deformations. Proposing a design method for the rib spacing in HBRB.